A Practical Tool to Enhance Faculty and Student Interactions Surrounding e-Learning Platforms. (September 2022) - Williams, Kimberly N.; Gombas, Alexandria K.; Cornejo Happel, Claudia; Parodi, Tracy C.; Lazzara, Elizabeth H.; Chaparro, Barbara S.
Learning management systems (LMS) are prevalent in modern day education, but their implementation is often highly diverse based on individual faculty and course needs. This can result in students falling behind in their schoolwork if they do not understand how faculty use the e-learning platform in specific courses, which may be further exacerbated when students are exposed to many different faculty using learning management systems in different ways at a single institution. The current research sought to create a practical tool to reduce the impact of diverse LMS implementation through the generation of a homepage template that could be customized across courses. We utilized focus groups and literature review to identify requirements and create the template. This template was implemented across a diverse set of classes and its impact is being assessed through surveys administered to faculty and students. From the faculty perspective, the template has been well received and the majority of faculty who have completed our feedback survey intend to continue to reuse the template in many of their courses.